Occupational disability in bipolar disorder: analysis of predictors of being on severe disablement benefit (PREBIS study data). (23rd August 2012) - Grande, I.; Goikolea, J. M.; de Dios, C.; González‐Pinto, A.; Montes, J. M.; Saiz‐Ruiz, J.; Prieto, E.; Vieta, E.; ,
<x xml:space="preserve">Abstract</x> Grande I, Goikolea JM, de Dios C, González‐Pinto A, Montes JM, Saiz‐Ruiz J, Prieto E, Vieta E, for the PREBIS group. Occupational disability in bipolar disorder: analysis of predictors of being on severe disablement benefit PREBIS study data). Objective: Patients diagnosed with bipolar disorder (BD) are reported to have significant work impairment during interepisode intervals. This study was carried out to assess potential predictors of occupational disability in a longitudinal follow‐up of euthymic patients. Method: We included 327 euthymic patients diagnosed with BD type I or type II, 226 of whom were employed and 101 were receiving a severe disablement benefit (SDB). Sociodemographic data were studied and episode recurrence was assessed along a 1‐year follow‐up. Logistic regression analysis was applied to determine predictors of receiving SDB. Cox regression was built to study recurrences. Results: Predictors of receiving SDB were: axis II comorbidity [Odds Ratio (OR) = 2.94, CI: 1.26–6.86, P = 0.013], number of manic episodes (OR = 1.21, CI: 1.10–1.34, P < 0.001), being without stable partner (OR = 2.44, CI: 1.34–4.44, P = 0.004) and older age (OR = 1.08, CI: 1.05–1.12, P < 0.001). Bipolar patients receiving SDB presented more episodic recurrences regardless of polarity than employed bipolar patients (P = 0.002). The time until recurrence in 25% of the bipolar patients receiving SDB was 6.08 months (CI: 4.44–11.77) being 13.08 months (CI: 9.60 to –) in the employed group. Conclusion: Occupational disability in bipolar patients is associated with axis II comorbidity, more previous manic episodes, not having a stable relationship, older age, and more recurrences at 1‐year follow‐up.